Morphological evaluation of genetic evidence for a Pleistocene extirpation of eastern African impala - Sally Reynolds (South African Journal of Science)
Palaeontology typically relies on fossil studies, in particular morphological differences, to reconstruct and interpret patterns of vertebrate evolution. However, genetic studies of population histories of extant species provide data about past population events (e.g. local extinctions, recolonisations) which are equally relevant to palaeontological questions. This study used morphological traits to evaluate a hypothesis based on genetic evidence that southern African impala (Aepyceros melampus) are the founder population for all other living African impala populations, after an eastern African extirpation event dating to around 200 000 years ago. Measurements of three horn metrics and the presence or absence of a particular dental trait were compared across four regional impala samples. Eastern African impala possess a unique combination of larger horns and a significantly higher occurrence of entostyles when compared to other impala populations. These traits are likely to have characterised a small group of founding impala which recolonised this region. This pattern appears consistent with the genetic evidence that a subset of the southern African impala gave rise to the eastern African populations. Other species with complex population histories, such as wildebeest, eland, topi and hartebeest may also therefore be expected to express variation in certain morphological traits in the fossil record because of similar patterns of recolonisations. The process of local extinction and subsequent repopulation over shorter timescales (102 - 103 years) may pass unnoticed in the fossil record, and lineages may appear uninterrupted. Instead, greater morphological variation within a species may be observed, which may be misinterpreted as reflecting a speciation event, or ecophenotypic variation. Combining data from genetic studies and palaeontology may provide further clues as to how faunal dispersals within Africa shaped the morphological variation in the fossil record, and how to best interpret such differences.